Integrated Business Development Strategies For Pharmacy And Medical Clinic Services: A Case Study Of GF RCB - Pratama, Fajar Maully; Dora, Yenny Maya (CV. Ulil Albab Corp, 2026)
This business plan aims to analyze the financial feasibility and development prospects of the GF Rancabolang Pharmacy and Medical Clinic (GF RCB) as an integrated health service(one-stop service) that combines medical practice and medicine provision. This plan was developed based on the increasingcommunity need for accessible, fast, andhigh-quality health services. The analysis was conducted using a quantitative approach through investment feasibility indicators, namely Payback Period, Net Present Value (NPV),Return on Investment (ROI), and Profitability Index (PI). The results of the calculationsshow that the initial investment of IDR 540,000,000 is feasible. The Payback Period was achieved in 1.26 years (±15 months), indicating a quick returnon investment. The NPV value of IDR 526,859,000 shows that the projectgenerates positive economic benefits, while the ROI of 79% and PI of 1.98 prove that this venture provides a high level of profit. The 2025–2029 financial projections show an increase in revenue from IDR 2.2billion to IDR 3.22 billion, as well as an increase in net profit after tax from IDR 429 million to IDR 761 million. Thus, the development of the GF Rancabolang Pharmacy and Clinicis declared feasible, profitable, and has long-term growth prospects.